PERBEDAAN HASIL BELAJAR EXAMPLE NON EXAMPLE TERHADAP SISWA KELAS 5 PADA MATA PELAJARAN IPA - Ina Lestari; Indri Anugraheni (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2017)
The problem in this research is "Differences of Cooperative Learning Outcomes Type Example Non Example Media Assisted Images Against 5th Grade Students of State Elementary School Bener 02 In Science Subject Semester II, with sub research problem that is, student learning outcomes control group on science subjects in Process materials Soil Formation due to weathering in 5th grade State Elementary School Bener 01, student learning outcomes experimental group on science subjects in the process of Soil Formation process due to weathering in 5th grade State Elementary School Bener 02 and Differences of control group learning outcomes with experimental group applying the model of learning Example Non Example media-aided images on science subjects in materials The process of Soil Formation due to weathering in 5th grade State Elementary School Bener. Variables in this study consisted of independent variables and dependent variables, this study using experimental methods, with the form of research is a quasi-experimental research. The experimental design used in this research is Pretest Posttest Control Group Design. Population in this research that is all student of class 5 which amounted to 63 student. This sampling technique using saturated sample technique. Data collection techniques used in this research are test, observation and documentation. Based on the analysis of data obtained: the average of control group learning outcomes amounted to 69,336, student learning outcomes in the experimental group amounted to 84.454, based on the calculation using t test in obtaining the value of significance / probability 0.000 less than 0.05 then H_0 rejected then Ha accepted. This means that there are differences in the results of science learning significance in grade 5 students of State Elementary School Bener 02 in learning using the model of learning Example Non Example.